Feature of Hortatory Text: A Sentence Element Pattern Analysis - Zico Ma?u, Jean Antunes Rudolf (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2018)
Text is an important part in learning language. In English, there are several types of texts which are considered to be complicated by readers. One of such texts is hortatory text. Hortatory text is related to the proposal of an individual?s argument. For some readers, this type of text might be complicated because in one sense it might be persuading but in the other sense it might only be suggesting. Due to the complication, through the study the researcher would like to describe the hortatory text by analysing the sentence elements that a hortatory text might have. In addition, the researcher would also like to analyse the word category and the tense that a hortatory text might contain in order to provide a complete description of the hortatory text. From the results of the analysis, the researcher found that the main sentence element patterns of a hortatory text are S ? P, S ? P ? Pre ? DO, and S ? P ? DO. Other findings are the patterns are filled with the pronoun ?we? which are mainly with the modality verb; and these patterns are also filled with the present and the present perfect tense.